ETIKA BELAJAR DALAM AL-QURâAN (Kajian Tafsir Maudhuâi) - Wiyono, Ahmad Hady (Jurnal al Hikmah, 2016)
This paper examines the ethics of learning in the Quran, the Quran does not explicitly mention that the study is ethical but there are some verses of Quran which discuss exaltation for someone who increase their knowledge. Humans when present on earth empty, and as time goes by the name of the process need to know, know that using ethics, which is still much to learn without the use of ethics. As when selecting teachers as instructors, the place will be studying. The Quran was revealed for the good of all mankind, it is not necessary to not understand what is in it. The Quran teaches mankind to be patient in learning, sincere in search of knowledge, and also explained in order to ask when finding something difficult case to understand the lesson. The companions of the Prophet when seeking knowledge, striving to always be in front when the prophet was about to deliver his message, to come at the beginning of the assembly.